Flora of Northumberland and Durham - Nathaniel John Winch (Pensoft Publishers, 2014)
The classical treatise "Flora of Northumberland and Durham" by Nathaniel John Winch is re-published through the innovative Advanced Books platform as an example of combining modern information technology together with historical scholarship to create a new sort of resource and data re-use.